Felisa López, une réfugiée espagnole à Rennes en 1937 - Jean-François Botrel (Cahiers de Civilisation Espagnole Contemporaine)
Using a few photos and family memory, we reconstruct, through a microhistorical approach, the reception conditions in Rennes, between June and October 1937, of a Basque refugee and her two children, the behavior of the administration and population, daily life and the transitory world that Felisa López, born in 1907, shared with more than 500 women and children forced to leave their country.